2020
DOI: 10.1021/acsami.9b18873
|View full text |Cite
|
Sign up to set email alerts
|

Bean Pod-Inspired Ultrasensitive and Self-Healing Pressure Sensor Based on Laser-Induced Graphene and Polystyrene Microsphere Sandwiched Structure

Abstract: Flexible pressure sensors are currently at the center stage of wearable electronics. Despite tremendous progress in the recent years, flexible pressure sensors with high sensitivity, high stability, and mechanical robustness are still challenging. In this paper, as inspired by the bean pod structure, a sensor architecture consisting a microspacer core layer of polystyrene (PS) microspheres, sandwiched between two laser-induced graphene/polyurethane (LIG/PU) films, is presented. A flexible and self-healable pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 48 publications
(71 reference statements)
1
65
0
Order By: Relevance
“…An alternative method of microengineering the active layer of resistive pressure sensors to improve performance is to introduce micropores. [ 44,87,112–114 ] Using FEM to simulate samples with different pore sizes, Kim et al found that modulus changes based on pore size and pore density. [ 87 ] Further, Visser et al found that modulus changes whether the overall structure is open‐cell or closed‐cell (Figure 9A).…”
Section: Resistive Pressure Sensorsmentioning
confidence: 99%
“…An alternative method of microengineering the active layer of resistive pressure sensors to improve performance is to introduce micropores. [ 44,87,112–114 ] Using FEM to simulate samples with different pore sizes, Kim et al found that modulus changes based on pore size and pore density. [ 87 ] Further, Visser et al found that modulus changes whether the overall structure is open‐cell or closed‐cell (Figure 9A).…”
Section: Resistive Pressure Sensorsmentioning
confidence: 99%
“…Piezoresistive transducers. The piezoresistance of LIG electrodes printed on flexible PI films has been exploited and utilized in a range of configurations, including measurements of strain, deflection, curvature, force, and pressure [86,89,90,94,97,103,105]. The high variation of the electrical resistance of multilayer samples under strain is induced by the displacement of the layers and changes of their overlapping area.…”
Section: Physical Sensors Made Of Ligmentioning
confidence: 99%
“…Adapted with permission. [174] Copyright 2020, American Chemical Society; e) SEM images of different parts of a printed synthetic spider's web. Adapted with permission.…”
Section: Microscopic Imitation Of Bulk Structuresmentioning
confidence: 99%
“…For instance, a bean pod-like configuration, where the "pod" is a conductive porous graphene network and the "beans" are insulating polymer spacers (Figure 9d), results in a good pressure-sensing behavior in both high-and low-pressure regimes because the conductance changes significantly as the spacers are compressed. [174] At the same time, the geometry can be tuned to provide spatial resolution. In a spider web, the radial threads, which provide structural support and transport vibrational signals, have a different structure to the flexible spiral threads, where prey is caught.…”
Section: Microscopic Imitation Of Bulk Structuresmentioning
confidence: 99%